Classical mechanics : an undergraduate text - Gregory, R. Douglas (Cambridge University Press, 2006)
This text provides a complete guide to mechanics, necessary for any applied mathematics student. Gregory has written a detailed account of classical analytical mechanics that will appeal to the modern student.